Advertisement quantity optimization to maximize profit in a Publishing House - Boff Medeiros, Natalia; Vidor, Gabriel (Brazilian Journal of Operations & Production Management, 2018)
This study aims to determine the optimal quantity of pages and the optimal quantity of each size advertisement that a magazine should have to maximize profit in a publishing house. The solution of this problem is based on operations research method application and is composed by four steps: (i) defining the problem, (ii) algorithm application, (iii) modeling scenarios and (iv) decision-making. The application of the method is performed in a publishing house data and the problem is solved by linear programming perspective. The results indicate that it is possible to maximize the total profit finding the optimal quantity of advertisements. The main contribution of the paper is to illustrate the use of operations research at service industries through a publishing house case. In conclusion, the method proposed to improve the ads allocation regarding the maximum profit.